Yowšabekorner, arjak êǰer ew ... - Hasrat̕yan, Morows 1902-1979 (Hratarakowt̕iwn Karpis L. Nazarean Himnadrami, 2007)
Biography and memoirs of the author of his contemporaries Eruand Shahaziz, Zoravar Andranik, Toros Toranean, Aksel Bakunts, Charents and others